Revitalisasi Kepemimpinan Pesantren: Kajian Peran Perempuan Dalam Transformasi Pendidikan Islam - Yani, Linda Yuli; Aimah, Siti; Setiawan, Andi (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2025)
This study aims to examine the role of women in the revitalization of Islamic boarding schools, especially in strengthening spiritual values, inclusivity, and community development at the Darussalam Blokagung Islamic Boarding School. This topic was chosen because women's leadership is considered strategic in supporting the transformation of Islamic education. The method used is qualitative with a case study approach, involving observation, in-depth interviews, and documentation. The results of the study indicate that women's leadership plays an important role in creating an environment that supports the strengthening of the morals and spirituality of students through an empathetic approach and role models. Women also lead inclusive programs such as skills training and social empowerment, which involve the surrounding community. Social challenges related to traditional norms were successfully overcome through the success of these programs, which strengthened community acceptance of women's leadership. This study contributes to the development of Islamic education strategies that are relevant to the needs of the times. The findings indicate that women's leadership not only enriches spiritual education but also builds an inclusive and sustainable Islamic boarding school community.